How's life? 2015. Measuring well-being (Paris, 2015)
"How’s Life? describes the essential ingredients that shape people’s well-being in OECD and partner countries. It includes a wide variety of statistics, capturing both material well-being (such as income, jobs and housing) and the broader quality of people’s lives (such as their health, education, work-life balance, environment, social connections, civic engagement, subjective well-being and safety). The report documents the latest evidence on well-being, as well as changes over time, and the distribution of well-being outcomes among different groups of the population.